Aktivitas Fisik Berhubungan dengan Kualitas Tidur pada Mahasiswa: Physical Activity is Associated with Sleep Quality in College Students - Rahma, Sania (Journal of Public Health Education, 2022)
Background: Based on research conducted on students at Indonesi Maju University, many students experience poor sleep quality, marked by frequent waking up in the middle of the night, inability to fall asleep within 30 minutes of lying down, and difficulty returning to sleep after waking up. Poor sleep disturbances can lead to various health hazards such as insomnia, hypersomnia, parasomnia, narcolepsy, sleep apnea, sleepwalking, sleep apnea, delayed sleep phase disorder, somnambulism, snoring, and nightmares. This research is important and can serve as a reference to improve physical activity and sleep quality among students with poor sleep quality. Objective: To determine the relationship between physical activity and sleep quality among students. Method: This research used a cross-sectional study design, with a population of 177 fifth-semester undergraduate students at Indonesia Maju University, and a sample of 118 students selected using the Slovin formula. Bivariate analysis was conducted using the Spearman's Rank Test. The instruments used were the International Physical Activity Questionnaire (IPAQ) to measure physical activity and the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. Results: The results of this study show a relationship between physical activity and sleep quality, with a p-value of 0.001 < α 0.005. Conclusion: It is concluded that there is a relationship between physical activity and sleep quality among adolescents. The majority of students at Indonesia Maju University have poor sleep quality and are not physically active. Therefore, with this research, students can be motivated to improve their physical activity and, consequently, their sleep quality.